Factors promoting and impeding efforts to deprescribe antidepressants among nursing home residents with dementia- a process evaluation guided by normalization process theory - Sinead Shahrzad; Gritt Overbeck; Anne Holm; Kirsten Høj; Pernille Hølmkjaer (BMC, 2024)
Abstract Background Despite recommendations against psychotropic medication in older nursing homes residents with behavioral and psychological symptoms of dementia (BPSD), antidepressants and other psychotropic drugs are still prescribed. We performed a cluster-randomized controlled trial to evaluate the effect of a complex intervention aiming to promote the deprescribing of antidepressants in institutionalized older persons with dementia. To understand the underlying mechanisms of trial outcomes, we conducted a process evaluation exploring the interventions implementation, areas of impact, and contextual factors. The aim of this study was to explore the implementation process and the key factors that promoted and inhibited intervention implementation in the care home setting (Clinicaltrials.gov: NCT04985305. Registered 30 July 2021). Methods Qualitative interviews were conducted between August 2022 and February 2023 with four general practitioners and eight nursing home staff from four associated nursing homes in the Capital Region of Denmark. We coded the interview data according to the four constructs of the Normalization Process Theory (coherence, cognitive participation, collective action, and reflexive monitoring). Results There was a common understanding of the intervention aim. We observed a raised awareness concerning the deprescription of antidepressants among healthcare professionals with good collaboration (coherence). An overall buy-in to a deprescribing mentality was seen (cognitive participation). There were barriers to the GPs and nursing home staff's use of the intervention elements and how they implemented it, but to some, a common language was created (collective action). Professionals overall valued the idea of deprescribing, but lack of time, high staff turnover, and low education level among nursing home staff hampered the integration (reflexive monitoring). Conclusion Successful implementation seemed to be dependent on the quality of the relationship between the single GP and the single nursing home professional. A common deprescribing mentality promoted the uptake of the intervention. However, several barriers related to lack of resources hindered implementation. It is imperative to adapt complex interventions to the available resources and context.